Behavioural Intention to Adoption of Digital Wallets in Nepal: An Application Using the UTAUT Model - Sanita Mastran; Bindu Bhandari (Journal of Business and Social Sciences, 2022)
Digital wallets in Nepal have expanded beyond just basic financial transactions. They are utilized for online purchases, utility bill payments, tax payments, renewal services, and many more. With the rapid growth of technology and the digital economy, digital wallet users are also growing (27.86%) within a year. Digital wallet users are self-assured to become a vital instrument in enhancing the quality of life for Nepali citizens and promoting financial inclusion. They are fast becoming an indispensable component of the country’s financial ecosystem. The purpose of this research was to examine the elements that influence behavioral intention to adopt digital wallets. Data was gathered from a group of 150 individuals from various regions of Nepal. The study relied on five independent variables (Performance expectancy, effort expectancy, social influence, facilitating condition, and trust) derived from the UTAUT model. Convenience sampling was used to gather the information. The result shows that the facilitating condition was not relevant in the adoption of digital wallets in Nepal. Similarly, the age factor of the users was more associated than the gender of the respondents with performance expectancy in the Nepalese context.